An Evaluation of the Role of School Institution in the Reproduction of Cultural-Social Inequalities and of Privileges - Eren Ağın; Duygun Göktürk (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study aims to examine the effects of institutional habitus on education in the context of cultural and social inequalities. Cultural and social inequalities, shaped by the determinants of social origin and social environment, are maintained within the school as an institutional structure. The school includes participation and certain types of behaviors formed under the influence of normative structures; has public influence, legitimacy and recognition; and as a stable structure is based on certain internal working mechanisms and assets. This article examines how forms of cultural and social inequality deepen within the school habitus, and how they become invisible through formal equality in the acquisition of knowledge and in the context of symbolic partnership. This study is based on three major texts: Pierre Bourdieu and Jean-Claude Passeron’s “The Inheritors: French Students and Their Relations to Culture”, Paul Willis’s “Learning to Labour: How Working-Class Kids Get Working Class Jobs”, and Signithia Fordham and John U. Ogbu’s “Black Students’ School Success: Coping with the Burden of Acting White.” This study reveals how social and cultural inequalities are reproduced within the school habitus through the determination of professional preferences based on students’ class, cultural habitus and reference codes, and informal group identities.